Cost-Efficient Fault-Tolerant Decoder for Hybrid Nanoelectronic Memories - Haron, Nor Zaidi; Hamdioui, Said (2011)
Existing work on fault tolerance in hybrid nanoelectronic memories (hybrid memories) assumes that faults only occur in the memory array and the encoder, not in the decoder. However, as the decoder is structured using scaled CMOS devices, it is also becoming vulnerable to faults. This paper presents a cost-efficient fault-tolerant decoder for hybrid memories that are impacted by a high degree of non-permanent clustered faults. Fault-tolerant capability is achieved by combining partial hardware redundancy scheme and on-line masking scheme based on Muller C-gates. In addition, the cost-efficient implementation of the decoder is realized by modifying the decoding sequence and implementing it based on time redundancy. Experimental results show that the proposed decoder is able to provide better reliability of the overall hybrid memory system, yet requires smaller area as compared to conventional decoder. For example, when assuming the fault ratio between decoder and memory array is 1:10 and at 10% fault rate, the proposed decoder ensures 1% higher reliability of the overall hybrid memory system. Moreover, the proposed decoder realizes 18.4% smaller area overhead for 64-bit word hybrid memory.